Pengaruh Komitmen Organisasional Terhadap Mediator Dalam Hubungan Kepuasan Kerja - Cahya, Nur (Economic Management Business Research Journal, 2025)
Many researchers in behavioural organizational science found that multidimensional effect of commitment variableseffective commitment; continuance commitment and normative commitmenthave different influence to turnover intention. This research aims to investigate influence multidimensional effect of commitment to turn over intention and to analyze multidimensional of commitment as mediator variables. Questionaires distribute among lectures and nurses of Sultan Agung Fondation amounting 59 respondents. The result using regression analysis find that all of multidimensional of commitment have no significance to turn over intention and discussed deeply in discussion session.